2018
DOI: 10.1002/cam4.1610
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor repertoire profiling predicts the prognosis of HBV‐associated hepatocellular carcinoma

Abstract: Tumor‐infiltrating T cell repertoire has been demonstrated to be closely associated with anti‐tumor immune response. However, the relationship between T cell repertoire in tumor tissue and prognosis has never been reported in Hepatocellular carcinoma (HCC). We performed the high‐throughput T cell receptor (TCR) sequencing to systematically characterize the infiltrating T cell repertoires of tumor and matched adjacent normal tissues from 23 HBV‐associated HCC patients. Significant differences on usage frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…Such impact has not been seen for OS, probably due to the small size of the cohort, but when we separated patients according to their early death or long survival, a significant association is visible, with a lower DR in patients who died early. In line with our data, in many tumor types, TCR repertoire diversity appears as a prognostic factor of clinical outcome in cancer patient, a high diversity being associated with a better prognosis (Cui et al, ; Jin et al, ; Keane et al, ; Lin et al, ; Manuel et al, ; Tamura et al, ). A high TCR repertoire diversity could reflect a good functionality of the immune system, increasing chances that a sub‐population immunologically pertinent should be present, leading therefore to a better anti‐tumor immune response.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Such impact has not been seen for OS, probably due to the small size of the cohort, but when we separated patients according to their early death or long survival, a significant association is visible, with a lower DR in patients who died early. In line with our data, in many tumor types, TCR repertoire diversity appears as a prognostic factor of clinical outcome in cancer patient, a high diversity being associated with a better prognosis (Cui et al, ; Jin et al, ; Keane et al, ; Lin et al, ; Manuel et al, ; Tamura et al, ). A high TCR repertoire diversity could reflect a good functionality of the immune system, increasing chances that a sub‐population immunologically pertinent should be present, leading therefore to a better anti‐tumor immune response.…”
Section: Discussionsupporting
confidence: 87%
“…A low TCR diversity (divpenia) is associated with a poor overall survival in breast cancer patients (Manuel et al, ). The similarity of the TCR repertoire profiling between tumor and adjacent normal tissue is associated with the prognosis in hepatocellular carcinoma (Lin et al, ). In nasopharyngeal carcinoma, a lower diversity of TCR repertoire in tumors compared to paired tissues and a higher diversity in peripheral blood are associated with a poor prognosis (Jin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used TCR sequencing to examine the intratumoral T cell response in solid cancers [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25], including in NSCLC [10,26,27]. TCR repertoire analysis has also been used as a biomarker, in the context of checkpoint blockade [28,29,30,31,32,33,34,35].…”
mentioning
confidence: 99%
“…However, a recent study that presented data from 15 lung cancer patients showed that significantly higher TCR diversity was observed in tumor tissues than in normal lung tissues, 32 the increases or decreases of the diversity of TCRs in tumors relative to paired normal tissues are inconsistent in different cancer types 33 , 34 , 35 or even same type in different studies. 16 , 17 For example, compared with adjacent non-tumor tissues, TCR diversity of tumors is decreased in colorectal cancer 33 and clear cell renal cell carcinomas, 34 increased or not changed in hepatocellular carcinoma with inconsistent results in two studies, 16 , 17 and not changed in esophageal squamous cell carcinoma. 35 These inconsistencies probably resulted from the intrinsic difference of T cell infiltration in paired tissues from distinct individuals and need to be confirmed in the future study.…”
Section: Discussionmentioning
confidence: 99%